Memories of combat: how World War II veterans construct their memory over time - Prosser, Michelle (Kansas State University, 2014)
Throughout the 1990s and into the twenty-first century, American society sought to record the stories of World War II veterans before they passed on. The United States Congress established the Veterans History Project in 2000 in order to collect stories not only from World War II veterans, but also from veterans of all wars. Although many similar programs existed before this one, this initiative stimulated the interest of communities all over the country to conduct oral history projects of their own. As a result, the availability of veterans’ accounts improved for scholars as well as for the general public. Along with veterans’ interviews, many collections include donated letters, diaries, and memoirs. Many of these institutions have posted their materials on the internet, thus giving easier public access to the sources. The increased availability of veterans’ accounts has shifted the question from, “What was the World War II veterans’ experience?” to “How do the veterans reflect on their experience?” This study analyzes the memories of World War II veterans who have documented their experiences at two separate times in their lives. It examines wartime letters and diaries written by soldiers as well as, oral histories conducted after the war. This study compares three veterans’ memories over time and the influence of collective memory on their remembrances. This case study finds that although these three veterans had very different experiences, they all reflected on their experience in similar ways. The veterans’ immediate accounts were straightforward and without introspection, while their later accounts included interpretation and analysis of their experiences. Although the details in each narrative are unique to the veteran, the overall tone and meaning of the memory constructed in their oral histories followed the meaning presented in the American collective memory of the war.
Keywords: World War IIHistory and memory; Veteran memory; History (0578)